DISPOSITIVO BIOSSENSOR, PROCESSO PARA MANUFATURAR UM DISPOSITIVO BIOSSENSOR, E MÉTODO PARA DETECTAR A PRESENÇA DE UM ANALITO EM UM FLUIDO DE AMOSTRA - GORDON T. JOWETT; WILHELMINA M. HARDEMAN; SANDRA MARLIN; THEA VAN DER WIJK; ALBERT H. J. IMMINK; EDUARD G. M. PELSSERS; FEMKE K. DE THEIJE (2015)
A system and method is described wherein components of the reagent (4), e.g. labelled antibodies, are separated from the biologically active sensor surface (5) by depositing the reagent (4) on a carrier surface (3) distinct from the sensor surface (5) in the detection region (2), e.g. detection chamber. In this way, a high assay reproducibility is obtained. By allowing a short, well-defined and controlled, pre-incubation time between the particles of interest, e.g. drugs, in the sample fluid (20) and the reagent (4), the reproducibility will be increased, whereas the speed of the assay is guaranteed by having all components in one detection region (2), e.g. detection chamber.